A GIS-based approach for integrating agriculture into urban and peri-urban planning - Forkuor, Gerald; Drechsel, Pay; Cofie, Olufunke O. (2011)
In most developing countries, zoning land for urban farming remains a major obstacle to urban and peri-urban agriculture. In this study, Geographical Information Systems (GIS) and Multi-Criteria Analysis are used to demonstrate how city authorities can integrate farming into their planning. The study was conducted in five districts in and around Ghana’s capital city. Spatial layers representing six influencing factors were created. Results indicate that, out of the five districts, Tema municipality has the highest percentage of suitable lands for agriculture while Akuapim South has the lowest. City authorities are encouraged to adopt the approach, as it would enable them to build and monitor different scenarios (with different factors and weights) in a participatory manner before and after planning decisions are made.